2021
DOI: 10.1111/psyp.13938
|View full text |Cite
|
Sign up to set email alerts
|

Working memory load reduces the processing of outcome evaluation involving others but not oneself: Event‐related potential evidence

Abstract: Previous event-related potential (ERP) studies have suggested that self-related and non-self-related outcomes are processed simultaneously. However, the studies investigated situations in which individuals had sufficient attentional/cognitive resources to process both of the outcomes. It is unknown whether self-related and non-self-unrelated outcomes could still be processed simultaneously when resources are limited. To address this issue, 32 female participants in the present study were asked to perform a wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 75 publications
(127 reference statements)
0
10
0
Order By: Relevance
“…For the other half, participants' performance outcomes were indicated by the ">" and "<" symbols, and the social comparison-related outcomes were signified by the "+" and "−" symbols. Note that for social comparison-related outcomes, using this presentation approach makes it easier for participants to process relevant outcomes than the approach used in previous studies, in which only outcomes involving others were presented (Lin & Liang, 2021c;Qi et al, 2018;Qiu et al, 2010;Valt et al, 2020;Wu et al, 2012;Zhang et al, 2020Zhang et al, , 2021.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the other half, participants' performance outcomes were indicated by the ">" and "<" symbols, and the social comparison-related outcomes were signified by the "+" and "−" symbols. Note that for social comparison-related outcomes, using this presentation approach makes it easier for participants to process relevant outcomes than the approach used in previous studies, in which only outcomes involving others were presented (Lin & Liang, 2021c;Qi et al, 2018;Qiu et al, 2010;Valt et al, 2020;Wu et al, 2012;Zhang et al, 2020Zhang et al, , 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the abovementioned ERP components have been used to investigate the processing of social comparison-related outcomes. Social comparison is often investigated by varying self-related and others' outcomes (Boksem et al, 2011;Lin & Liang, 2021c;Qi et al, 2018;Qiu et al, 2010;Valt et al, 2020;Zhang et al, 2020Zhang et al, , 2021. Using this approach, Boksem et al (2011) revealed an effect of others' outcomes on FRN and P300 responses irrespective of self-related outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy individuals, social comparison increases or decreases the value of the consequences of own actions and performances depending on the outcomes of others [41][42][43][44][45][46][47][48]. Previous neuroimaging studies have shown that social comparison influences striatal activationsin particular, activations of the putamen and ventral striatumduring feedback processing [49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…A study of eyetracking design showed that individuals with high WM capacity performed better in resisting interference than individuals with low WM capacity (15). When the load of WM generates a gradient, in low-order working memory tasks, whether MDD patients with impaired interference control can control the central executive resources to complete the low-order WM tasks is not clear (22). Therefore, exploring the mechanism of interference control impairment and specifying the possible performance of MDD under different WM gradients will be of great help to better refine WM training and treatment plans in the future.…”
Section: Introductionmentioning
confidence: 99%